Conclusions: The key role of agriculture in achieving better diets in Malawi - Harris, Jody; Aberman, Noora-Lisa (International Food Policy Research Institute, 2018)
This report combines international evidence with new primary and secondary analyses of Malawian data to understand the different pathways linking agriculture, food security, and nutrition for households in Malawi and to illuminate different dimensions of these links. In addition to outlining different theoretical and methodological approaches to studying these connections, this report provides evidence on the role of commodity production, food prices, agricultural diversification, and irrigation in changing household food security and access to different nutrients, as well as impacts on individual diets and nutrition. This chapter provides a summary of the empirical chapters, draws out some key themes, and suggests some implications for Malawi and other countries with a large agriculture sector that concurrently face issues of food insecurity, hunger, and malnutrition.